What Can Be Achieved By Special R&D Funds When There is No Special Leaning Towards R&D Intensive Industries? - Rahel Falk; Hannes Leo (Austrian Institute of Economic Research (WIFO), 2006)
This paper explores the effects of Austria's recent Special Funds initiative on the R&D expenditures of its private corporate sector. It is the first one to approach the due evaluation from a macro perspective. First, simple descriptive statistics show that the noticeable delays in actual disbursements and the replacement of regular RTI funds by these special funds reduce the latter's scope. Apparently, money can't work unless it is spent and "additional" funds at the expense of regular funds will trigger no additionalities. We then set up an econometric model to derive some inference on the relative importance of different public support channels on the business sector's R&D spending. Though the estimates suggest that direct government subsidies to R&D-performing firms unfold great leverage effects, the dynamics of output growth as well as an R&D-prone high-tech industry structure seem to be more important drivers of the business sector's R&D intensity. Likewise, feeding special funds into the higher education sector will raise the R&D-intensity of the business enterprise sector only if and to the degree that such funds contribute to Austria's overall economic prosperity or foster structural change towards more R&D-intensive manufacturing.
Keywords: 330; R&D funds; R&D intensity; Technologiepolitik; Wirkungsanalyse; Österreich